(untitled) (Research, Society and Development, 2021)
Active methodology is a pedagogical method that uses real or fictitious facts as a teaching-learning strategy, aiming to reflect on a situation that has different possibilities for analysis to solvethe focused issue. Considering that these experiences are part of the construction of the subject’s personality, the challenges faced by this teaching method could interfere in the students’ affective and emotional temperamental dimensions. Thus, the present study evaluated the affective and emotional temperament of students enrolled in the first year of the Federal University of Sergipe (Campus Universitário Professor Antônio Garcia Filho), which uses different active methodologies, especially Problem Based Learning (PBL). There was a negative impact of PBL on students’ emotional temperament (willingness, control, coping, sensitivity and Global Emotional Functioning indicator). However, there was an increase/favoring of disinhibition and euphoria after the active methodology experience by the students. Hence, theactive methodology inherents aspects can contribute positively or negatively in certain dimensions of the affective and emotional temperament. Nonetheless, other studies in different academies, as well as the comparison with other current teaching methodologies are important to attest the effect of active methodology on temperament.